Analisis Volume Udara yang Dibutuhkan Blower dalam Pemindahan Tepung Tapioka dari Unit Dryer ke Unit Shifter - Tarigan, Nurlianna; Silitonga, Nelson; Sitorus, Ivo Jones (CV. IRA PUBLISHING, 2025)
This study aimed to calculate the volume of air required by a blower to transfer tapioca flour from the dryer unit to the shifter unit in a factory with a production capacity of 35 tons per day. The flour transfer process utilizes a blower to generate sufficient airflow. Still, it often experiences instability caused by factors such as blower speed fluctuations, material load variations, and pipe blockages. The research was conducted over one month using data collection methods that included interviews and direct observation. Analysis results showed that the cross-sectional area of the blower pipe was 0.6358 m², the airflow velocity was 1.517 m/s, and the airflow rate reached 0.965 m³/s. The total air volume required by the blower to move the flour was calculated to be 27,792 m³ per day. The findings highlight the importance of properly regulating and maintaining the blower system to ensure efficiency in tapioca flour production.